Indicators for examining links between agriculture, food security, and nutrition - Meerman, Janice; Aberman, Noora-Lisa; Harris, Jody; Pauw, Karl (International Food Policy Research Institute, 2018)
How can the nutrition impactof agriculture programsbe assessed? Depending on context, data may need to be collected on production practices for food, livestock, and cash crops; post–farm gate value chain and other market-based activities; commodity prices; household food security; women’s empowerment; dietary quality and quantity, and nutritional status. This chapter provides a primer3 on commonly used indicators for these processes and outcomes: diet and nutritional status; household food security; gender, household decision making, and empowerment; agricultural production, productivity, and diversification; and food markets and prices. The importance of dietary quality as a key intermediary between agriculture and nutrition is emphasized throughout this chapter. Individual dietary quality is best measured by dietary diversity as dietary diversity indicators have been repeatedly validated as predictive of nutritional adequacy. Individual dietary quality is a key outcome to measure the success of most agricultural programs and policies, if an impact on population well-being is desired. However, in many countries the surveys which collect data on individual dietary patterns (and other nutrition indicators) are not the same as those which collect information on agricultural production. While justifiable from a sectoral perspective, this “data disconnect” poses a challenge to analyzing agriculture–nutrition links.